Low-Chill Apple Cultivars for North Florida and North Central Florida: HS764/MG368, rev. 11/2022 - Andersen, Peter C.; Shahid, Muhammad A.; Folta, Kevin (EDIS, 2022)
This article will provide the information about different low chill apple cultivars suiable for north and central Florida